Rhinogenic Contact Point Headache: Surgical Treatment Versus Medical Treatment. Issue 3 (May 2018) - La Mantia, Ignazio; Grillo, Calogero; Andaloro, Claudio
Abstract : Abstract: Rhinogenic contact point headache (RCPH) is a headache syndrome secondary to mucosal contact points in the sinonasal cavities, in the absence of inflammatory signs, hyperplastic mucosa, purulent discharge, sinonasal polyps, or masses. It may result from pressure on the nasal mucosa due to anatomic variations among which the septal deviation, septal spur, and concha bullosa, are the most commonly observed. In recent years, RCPH has remained a subject of controversy regarding both its pathogenesis and treatment. This study aimed to investigate the effect of surgical and medical treatment of pain relief in patients with RCPH, evaluating the intensity, duration, and frequency of headaches, and the impact of different treatments on quality of life. Ninety-four patients with headache, no symptoms or signs of acute and chronic sinonasal inflammation and who present with intranasal mucosal contact points positive to the lidocaine test were randomized into 2 equal groups and given medical or surgical treatment. The authors used visual analog scale, number of hours, and days with pain to characterize the headache and Migraine Disability Assessment score (MIDAS) to assess the migraine disability score before and 3 to 6 months after treatment. After treatment the severity, duration, and frequency of the headache decreased significantly ( P  < 0.001, P  < 0.001, and P  = 0.031, respectively) as well as the MIDAS in the surgical group compared with medical group. Our results suggest that surgical removal of mucosal contact points is more effective than local medical treatment improving the therapeutic outcomes in patients with contact point headache.